"We Ask for More Than We Give Back": Negotiating the Boundaries of Informal Childcare Arrangements. (May 2021) - Cosson, Barbara; Cook, Kay; Brady, Michelle
There is an assumption that childcare services and workplace flexibility policies enable a seamless shift between childcare and work. Similarly, there is an assumption that informal care arrangements will be relatively seamless as the norm of reciprocity is assumed to bind families together through the bonds of love and affection. Monetary exchange for this work is seen to demean the caring relationship, but this does not mean "costs" are absent. Drawing on the work of Viviana Zelizer, this article examines how parents negotiate informal care arrangements, identifying the "payments" that differentiate family from friend care. The analysis focuses on parents working nonstandard and variable hours who were part of a broader project examining childcare flexibility, which also involved childcare providers and policymakers. This article identifies the relational work involved in the maintenance of informal care relationships and how they are negotiated when parents "ask for more than they give."